Student-Created Video Assessment Tools to Improve Critical Thinking, Social Awareness, Adaptability, and Technology Fluency - Mujahidil Mustaqim; SM. Wardatul Fauziah; Rina Patriana Chairiyani (LPPM Undiksha, 2025)
Academic dishonesty has become a persistent challenge for teachers in the era of rapid advancements in information technology. When learning continues to rely on traditional written assessments, students can easily access answers using emerging technologies such as artificial intelligence. The primary aim of this study is to evaluate the contribution of student-generated video (SGV) as an assessment tool to the development of critical thinking, social awareness, adaptability, and digital and technological fluency. This study involved 81 respondents and employed regression statistical analysis. The research began with the implementation of SGV as an assessment tool in classroom instruction. The results indicate that SGV exerts a measurable influence on each of the targeted skills, as evidenced by statistical values, demonstrating that SGV is capable of stimulating the development of these four competencies, although the magnitude of its contribution has not yet reached an optimal level. The limited frequency of SGV implementation is identified as a plausible factor underlying this outcome. Nevertheless, the findings highlight that SGV can serve as a valid and reliable alternative assessment method to reduce the increasingly widespread practice of academic dishonesty among students. This form of assessment is also highly applicable to contemporary learners who have grown up in technologically advanced environments and can be implemented across disciplines. The implications of this study suggest that video-based assessment can serve as an innovative strategy in 21st-century learning.